DEVELOPMENT OF CHEERFUL BOX MEDIA USING QR CODE TECHNOLOGY TO EMBED GEOMETRY CONCEPTS IN ELEMENTARY SCHOOLS - Mustaqimah, Rivanatul; Muhroji, Muhroji (Prima: Jurnal Pendidikan Matematika, 2025)
This research aims to produce a learning media product, the Cheerful Box, with QR Code technology to instill the concept of geometry in elementary schools. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research were class II students at MIM Krakitan, Bayat. The research data were obtained from observation, interviews, expert validation, pretest-posttest questions, and student response questionnaires to the developed media products. The data analysis techniques used are qualitative and quantitative. Qualitative data analysis techniques used interactive analysis at the product development stage and content analysis at the product appraisal stage, while quantitative data analysis techniques used expert validation tests at the product trial stage and testing with a paired sample t-test at the product assessment stage. The results showed that the learning media of the Cheerful Box with the QR Code technology that was developed was worth it and very valid, with an average score of 90% for material expert validation and 89% for media expert validation. This learning medium is also declared effective for instilling the concept of geometric shapes and shapes in elementary schools, as the results of the paired sample t-test show a significance value (2-tailed) of 0.000 <  0.05, so there is a significant difference between the average pretest-posttest results, and there is a significant effect of the use of the Cheerful Box learning media with QR Code technology on the results of students' understanding of geometric shapes and geometric shapes in elementary schools.